2012
DOI: 10.1115/1.4007063
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Rotordynamic Coefficients of Pocket Damper Seals Using the Multifrequency, One-Dimensional, Whirling Orbit Model and RANS Solutions

Abstract: The numerical approach using the muitifrequency one-dimensional whirling orbit model and Reynolds-averaged Navier-Stokes (RANS) solution was proposed for prediction of rotordynamic coefficients of pocket damper seal (PDS). By conducting the multiple frequencies one-dimensional whirling orbit for rotor center as the excitation signal, the unsteady RANS solutions combined with mesh deformation method were utilized to calculate the transient response forces on the PDS rotor surface. Unlike the single frequency wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…着节能降耗的关键作用 [1] 。 随着机组容量及工质参 数的不断提高,密封引起的气流激振问题日益突 出,密封气流激振已经成为发展高性能透平机械 * 国家自然科学基金资助项目(51875361, 51575105, 51676131)。 20190606 收到初稿,20190925 收到修改稿 的瓶颈 [2][3][4] 。密封的稳定性研究对进一步提升透平 机械可靠性具有重要意义。 钟明磊等 [5] 采用数值模拟方法建立了涡动转 子-迷宫密封三维模型,计算分析了不同结构高低 式迷宫密封气流激振力特点。 张万福等 [6] 建立了气 缸-密封系统动力学分析模型,提出一种新的密封 气流力及刚度系数识别方法,并应用双控制体模 型对偏心密封腔内压力分布及切向气流力产生机 理进行分析,并阐述了转速、进气压力、偏心、 密封间隙等因素对切向气流力的影响。 王庆峰等 [7] 基于稳态计算流体力学方法研究了压差对旋转直 通式迷宫气封泄漏、流场和流场力的影响,研究 结果表明:随着压差的增大,泄漏量、径向流体 压力、轴向流体压力、总流体压力和总流体粘滞 力均增大。 马文生等 [8] 采用数值方法计算得到迷宫 密封在五种偏心率与转速下的压力分布、密封力 的变化情况,并对影响泄漏量与动力学参数的因 素进行分析。 孙丹等 [9] 研究了偏心率对迷宫密封动 力特性及转子稳定性的影响,并提出新型浮式自 同心密封结构。 高性能计算机的不断发展,进一步推动了计算 流体力学的应用。从早期基于有限差分、有限体积 等方法的小规模编程计算 [10][11] ,到目前以大型商业 计算软件为主的 CFD 三维湍流模拟。 密封流场计算 方法主要有如下两种: 瞬态涡动法: 该方法基于 CFD 非稳态求解及动 网格方法,对密封内流场进行计算 [12][13][14] 。如果在固 定坐标系下求解,计算域参数属于非稳态,则需要 采用动网格技术对密封流场进行非定常求解,具有 较高的计算难度。 旋转坐标系法:该方法应用旋转坐标系将转子 实际的非稳态涡动问题转变为准稳态模型,计算速 度较快 [15][16] [18] 。 在(x, y)坐标系中,设转子轴心涡动轨迹方程为 cos( ) sin( )…”
Section: 非接触式密封作为汽轮机、航空发动机、压 缩机等旋转机械中抑制工质泄漏的重要部件,起unclassified
“…着节能降耗的关键作用 [1] 。 随着机组容量及工质参 数的不断提高,密封引起的气流激振问题日益突 出,密封气流激振已经成为发展高性能透平机械 * 国家自然科学基金资助项目(51875361, 51575105, 51676131)。 20190606 收到初稿,20190925 收到修改稿 的瓶颈 [2][3][4] 。密封的稳定性研究对进一步提升透平 机械可靠性具有重要意义。 钟明磊等 [5] 采用数值模拟方法建立了涡动转 子-迷宫密封三维模型,计算分析了不同结构高低 式迷宫密封气流激振力特点。 张万福等 [6] 建立了气 缸-密封系统动力学分析模型,提出一种新的密封 气流力及刚度系数识别方法,并应用双控制体模 型对偏心密封腔内压力分布及切向气流力产生机 理进行分析,并阐述了转速、进气压力、偏心、 密封间隙等因素对切向气流力的影响。 王庆峰等 [7] 基于稳态计算流体力学方法研究了压差对旋转直 通式迷宫气封泄漏、流场和流场力的影响,研究 结果表明:随着压差的增大,泄漏量、径向流体 压力、轴向流体压力、总流体压力和总流体粘滞 力均增大。 马文生等 [8] 采用数值方法计算得到迷宫 密封在五种偏心率与转速下的压力分布、密封力 的变化情况,并对影响泄漏量与动力学参数的因 素进行分析。 孙丹等 [9] 研究了偏心率对迷宫密封动 力特性及转子稳定性的影响,并提出新型浮式自 同心密封结构。 高性能计算机的不断发展,进一步推动了计算 流体力学的应用。从早期基于有限差分、有限体积 等方法的小规模编程计算 [10][11] ,到目前以大型商业 计算软件为主的 CFD 三维湍流模拟。 密封流场计算 方法主要有如下两种: 瞬态涡动法: 该方法基于 CFD 非稳态求解及动 网格方法,对密封内流场进行计算 [12][13][14] 。如果在固 定坐标系下求解,计算域参数属于非稳态,则需要 采用动网格技术对密封流场进行非定常求解,具有 较高的计算难度。 旋转坐标系法:该方法应用旋转坐标系将转子 实际的非稳态涡动问题转变为准稳态模型,计算速 度较快 [15][16] [18] 。 在(x, y)坐标系中,设转子轴心涡动轨迹方程为 cos( ) sin( )…”
Section: 非接触式密封作为汽轮机、航空发动机、压 缩机等旋转机械中抑制工质泄漏的重要部件,起unclassified
“…To maximize the rotordynamic and leakage performance, studies on the geometry optimization [7,[15][16][17] of pocket damper seals also were carried out. For an efficient calculation of seal characteristics, numerical methods, including the bulk-flow model (BFM) [6,[18][19][20] and CFD method [15][16][17][21][22][23][24], have been employed in recent years to predict the leakage and rotordynamic performance of pocket damper seals operating with various geometry, pressure ratio, rotational speed, inlet preswirl, and wet gas conditions. There are mainly two methods, including swirl brakes and shunt injection, to suppress the circumferential flow in annular gas seals.…”
Section: Introductionmentioning
confidence: 99%
“…These above transient CFD methods are all single-frequency whirl methods. In order to reduce calculation time, Li et al [21] used a transient CFD method based on a multiple-frequency 1D whirl model for rotordynamic coefficients of pocket damper seals and then the author applied this method to labyrinth seals and hole-pattern seals based on a multiple-frequency elliptical whirl model [22]. Comparing the experimental data and the numerical simulation data demonstrated that the numerical method with the multiple-frequency elliptical whirl model is available for predicting rotordynamic coefficients of annular gas seals in turbomachinery.…”
Section: Introductionmentioning
confidence: 99%